Generalized classes of suborbital graphs for the congruence subgroups of the modular group - Jaipong, P.; Tapanyo, W. (Algebra and Discrete Mathematics, 2019)
Let Г be the modular group. We extend a nontrivial Г-invariant equivalence relation on Q to a general relation by replacing the group Г₀(n) by Гк(n), and determine the suborbital graph Fᴷu,n, an extended concept of the graph Fu,n. We investigate several properties of the graph, such as, connectivity, forest conditions, and the relation between circuits of the graph and elliptic elements of the group Гк(n). We also provide the discussion on suborbital graphs for conjugate subgroups of Г.